Uranium Metalla-Allenes with Carbene Imido R2C=UIV=NR′ Units (R=Ph2PNSiMe3; R′=CPh3): Alkali-Metal-Mediated push–pull effects with an Amido Auxiliary - Lu, Erli; Tuna, Floriana; Lewis, William; Kaltsoyannis, Nikolas; Liddle, Stephen T. (Wiley, 2016)
We report uranium(IV)-carbene-imido-amide metalla-allene complexes [U(BIPMTMS)(NCPh3)(NHCPh3)(M)] (BIPMTMS=C(PPh2NSiMe3)2; M=Li or K) that can be described as R2C=U=NR′ push–pull metalla-allene units, as organometallic counterparts of the well-known push–pull organic allenes. The solid-state structures reveal that the R2C=U=NR′ units adopt highly unusual cis-arrangements, which are also reproduced by gas-phase theoretical studies conducted without the alkali metals to remove their potential structure-directing roles. Computational studies confirm the double-bond nature of the U=NR′ and U=CR2 interactions, the latter increasingly attenuated by potassium then lithium when compared to the hypothetical alkali-metal-free anion. Combined experimental and theoretical data show that the push–pull effect induced by the alkali metal cations and amide auxiliary gives a fundamental and tunable structural influence over the C=UIV=N units.